Nawacita, Pancasila, dan Ideologi Politik Pembangunan Nasional - Lestanta Budiman; Hastangka Hastangka (CIVICUS : Pendidikan-Penelitian-Pengabdian Pendidikan Pancasila dan Kewarganegaraan, 2020)
Pembangunan suatu bangsa tidak lepas dari ideologi politik yang diletakkan. Ideologi politik ini dapat berpengaruh dalam mengarahkan dan membentuk paradigma pembangunan nasional. Di Indonesia, politik pembangunan nasional selalu dipengaruhi oleh ideologi dan politik penguasa. Penguasa pada setiap zaman atau periode pemerintahan memiliki dasar ideologis dan politik yang unik dan khas dalam menjalankan pemerintahannya. Studi tentang pembangunan selama ini memang tidak terlalu banyak membahas peran dan pengaruh ideologi dan politik di dalamnya. Studi pembangunan yang berkembang selama ini bergerak pada tiga arus utama yaitu ekonomi, lingkungan, dan tata ruang wilayah atau tata ruang kota. Pembahasan tentang paradigma pembangunan atau pengarusutamaan pembangunan merujuk pada dua posisi yaitu posisi global, dimana peran global mengarahkan paradigma pembangunan yang selama ini berkembang di bebagai negara negara di dunia. Kemajuan negara negara yang memiliki standar hidup dan ekonomi yang tinggi dapat mempengaruhi paradigma dan model pembangunan yang ada di seluruh kawasan atau benua. Penelitian ini bertujuan untuk mendeskripsikan dan menggali garis ideologi dan politik yang diletakkan oleh pemerintah dalam membangun gagasan pembangunan nasional yang berkeadilan sosial melalui konsepsi Nawacita dan Pancasila. Metode yang digunakan dalam penelitian ini menggunakan pendekatan kualitatif. Analisis data yang digunakan dalam penelitian menggunakan interpretasi, analisis kebijakan, dan korelasi. Data yang digunakan berupa buku teks, jurnal, laporan ilmiah, dan peraturan perundang undangan. Hasil penelitian ini diharapkan dapat memperlihatkan relasi antara Nawacita, Pancasila dalam praktek ideologi politik pembangunan. The development of a nation is inseparable from the political ideology laid down. This political ideology can influence in directing and shaping the paradigm of national development. In Indonesia, the politics of national development has always been affected by the authorities' ideology and politics. The police in each era or period of government has a unique and unique ideological and political basis in carrying out their government. The study of development has not discussed too much the role and influence of ideology and politics in it. Development studies that have developed so far are engaged in three main currents: economy, environment, and regional or city spatial planning. The discussion of the development paradigm or the mainstreaming of development refers to two positions, namely the global situation, where the global role directs the development paradigm that has been developing in various countries in the world. Countries with high standards of living and economy can influence the development of paradigms and models that exist in all regions or continents. But a government that has not been fortunate or is still in the process of progressing towards the goals and objectives of the state tries to put its development paradigm on two legs. On the first foot, try to use the prescription of a global development paradigm. On the other hand, it uses the development paradigm, which is owned by the nation itself with the ideological and political lines laid by the authorities. In Indonesia, the idea of the ideology and politics of national development in the context of President Jokowi's administration spread an interesting ideological and political line, Nawacita. Nawacita is an ideal set forth in 9 agendas that are used as a reference and state ideological direction. This nawacita needs to be seen in the framework of national development. This study aims to describe and explore the government's ideological and political lines in building the idea of national development with social justice through the conception of Nawacita and Pancasila. The method used in this study uses a qualitative approach. Analysis of the data used in research uses interpretation, policy analysis, and correlation—the data used in the form of textbooks, journals, scientific reports, and legislation. This study's results are expected to show the relationship between Nawacita, Pancasila in the practice of political development ideology.